2020
DOI: 10.1021/acs.jpclett.9b03883
|View full text |Cite
|
Sign up to set email alerts
|

Revealing Hot and Long-Lived Metastable Spin States in the Photoinduced Switching of Solvated Metallogrid Complexes with Femtosecond Optical and X-ray Spectroscopies

Abstract: An atomistic understanding of the photoinduced spin-state switching (PSS) within polynuclear systems of d 4 -d 7 transition metal ion complexes is required for their rational integration into light-driven reactions of chemical and biological interests. However, in contrast to mononuclear systems, the multidimensional dynamics of the PSS in solvated molecular arrayshave not yet been elucidated, due to the expected complications associated to the connectivity between the metal centers and the strong interactions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 66 publications
2
10
0
Order By: Relevance
“…[31][32][33] Additionally, a combination of transient optical-infrared absorption and X-ray emission spectroscopy in solution has demonstrated that strongly linking several metal centres into metallogrids can be developed as an efficient synthetic strategy to increase the lifetime of the photoinduced metastable spin-state. 34,35 However, the aforementioned studies do not provide information on the complex pathway from molecular to materials scales accompanying the non-stationary photoinduced spin transition, while temperature dependent studies at equilibrium conditions only provide partial information on the structural changes. A general picture of the structural changes that accompany the equilibrium and out-of-equilibrium spin transition in the solid state of oligometallic systems is essential to understanding their structure-property relationships, which is necessary to design new materials with bi-or multistability in a targeted approach.…”
Section: Introductionmentioning
confidence: 99%
“…[31][32][33] Additionally, a combination of transient optical-infrared absorption and X-ray emission spectroscopy in solution has demonstrated that strongly linking several metal centres into metallogrids can be developed as an efficient synthetic strategy to increase the lifetime of the photoinduced metastable spin-state. 34,35 However, the aforementioned studies do not provide information on the complex pathway from molecular to materials scales accompanying the non-stationary photoinduced spin transition, while temperature dependent studies at equilibrium conditions only provide partial information on the structural changes. A general picture of the structural changes that accompany the equilibrium and out-of-equilibrium spin transition in the solid state of oligometallic systems is essential to understanding their structure-property relationships, which is necessary to design new materials with bi-or multistability in a targeted approach.…”
Section: Introductionmentioning
confidence: 99%
“…Still, the final proof for the existence of such an MC state has to be proven by more sensitive methods like ultrafast X‐ray emission spectroscopy. [33] …”
Section: Resultsmentioning
confidence: 99%
“…[9][10][11][12][13] Metallosupramolecular grids [14][15][16] are a particular class of self-assembled architectures that have attracted major interest due to their redox, magnetic or spin-state transition properties. [17][18][19][20][21][22][23][24][25] The construction of such metal ion arrays is based on the mutual recognition of directional ligands (L) and metal ions (M) leading to an orthogonal arrangement of the ligands at each metal corner. The [2 × 2] grids (Figure 1) are archetypes of this family of molecules.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, an impressive variety of self‐assembled metallo‐architectures have been reported including linear and circular helicates, [3,4] topological non‐trivial molecules, [5–7] metallo‐squares, [8] cages or giant spheres [9–13] . Metallosupramolecular grids [14–16] are a particular class of self‐assembled architectures that have attracted major interest due to their redox, magnetic or spin‐state transition properties [17–25] . The construction of such metal ion arrays is based on the mutual recognition of directional ligands (L) and metal ions (M) leading to an orthogonal arrangement of the ligands at each metal corner.…”
Section: Introductionmentioning
confidence: 99%